2015
DOI: 10.1142/s0217732315501102
|View full text |Cite
|
Sign up to set email alerts
|

Covariant asymmetric wave packet for a field-theoretical description of neutrino oscillations

Abstract: We consider a class of models for the relativistic covariant wave packets which can be used as asymptotically free in and out states in the quantum field theoretical formalisms for description of the neutrino flavor oscillation phenomenon. We demonstrate that the new "asymmetric" wave packet (AWP) is an appropriate alternative to the more conventional "symmetric" wave packets, like the so-called relativistic Gaussian packet (RGP) widely used in the QFT-based approaches to neutrino oscillations. We show that RG… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 50 publications
0
12
0
1
Order By: Relevance
“…Neither of these approaches has an advantage of explicit Lorentz invariance, although covariant generalization of the Gaussian wave packets seems to be feasible [80,81].…”
Section: Jhep03(2017)049 7 Summary and Outlookmentioning
confidence: 99%
“…Neither of these approaches has an advantage of explicit Lorentz invariance, although covariant generalization of the Gaussian wave packets seems to be feasible [80,81].…”
Section: Jhep03(2017)049 7 Summary and Outlookmentioning
confidence: 99%
“…A simple example is discussed in Ref. [30] within the so-called contracted relativistic Gaussian packet (CRGP) model [33,34]. It is in particular shown that σ eff is defined through the transverse (with respect to the neutrino propagation direction l) components of the inverse overlap tensors which determine the effective space-time overlap volumes of the WP states in the vertices of the macrodiagram.…”
Section: A Sketch Of the Qft Approachmentioning
confidence: 99%
“…The key ingredient of the formalism are covariant wave packets used to describe the quantum states of the initial and final particles involved in the neutrino production and detection processes. Many studies have been devoted to the development of this aspect of the theory (see, e.g., [152][153][154][155][156][157] and references therein), which extends well beyond the narrow topic of neutrino oscillations.…”
Section: Why Quantum Field Theory?mentioning
confidence: 99%